Cell Cycle Dynamics of the Nuclear Envelope - Roland Foisner (The Scientific World Journal)
The nuclear envelope (NE) consists of an inner and an outer membrane, nuclear pore complexes, and the underlying nuclear lamina, a filamentous scaffold structure formed by lamins. The inner membrane is linked to the lamina and chromatin by its integral membrane proteins, such as lamin B receptor (LBR), emerin, and various isoforms of lamina-associated polypeptides (LAP) 1 and 2, which bind lamins and/or chromatin. During mitosis, the NE is disassembled upon phosphorylation of its core components, and the NE is torn apart by a dynein-driven microtubule-dependent mechanism. Nuclear reassembly after sister chromatid separation requires a timely coordinated and dephosphorylation-dependent association of lamin-binding proteins and lamins with chromosomal proteins and targeting of membranes to specific sites on chromosomes. Various chromatin-binding domains in lamina proteins, such as the LEM domain, present in all LAP2 isoforms and in emerin, as well as unique regions in lamina proteins and in specific LAP2 isoforms have been implicated in defined steps of NE reformation. Furthermore, novel mechanisms of membrane fusion involving Ran GTPase are just beginning to emerge.